Electrophysiological profile of the patients with MuSK positive myasthenia gravis. (November 2014) - Nikolic, Ana; Basta, Ivana; Stojanovic, Vidosava Rakocevic; Stevic, Zorica; Lavrnic, Dragana
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: To determine the electrophysiological profile of our cohort of patients with muscle-specific tyrosine kinase (MuSK) positive myasthenia gravis (MG). Methods: Repetitive nerve stimulation test (RNS) and jitter analysis using concentric needle electrode were performed in 31 MuSK and in 28 acetylcholine receptor (AChR) positive MG patients. Results: Pathological RNS was verified in 16 (51·6%) MuSK and 26 (92·9%) AChR MG patients (P < 0·01). Pathological jitter analysis was registered in 28 (90·3%) MuSK and 26 (92·9%) AChR MG patients (P > 0·05). Increased jitter was present in extensor digitorum communis (EDC) in 23 (74·2%) MuSK and in 25 (89·3%) AChR MG patients (P > 0·05) as well as in orbicularis oculi (OO) muscle in 24 (85·7%) MuSK and 22 (81·5%) AChR MG patients (P > 0·05). Lower mean value of mean consecutive difference (MCD) and fewer potential pairs with increased jitter were registered in MuSK MG compared to AChR MG patients only in EDC muscle (P < 0·05). In MuSK MG patients, increased jitter was observed to be more frequent in patients with longer disease duration (P < 0·05) and also in those patients exhibiting more severe disease forms (P < 0·01) only in EDC muscle. Discussion: Repetitive nerve stimulation test has low sensitivity in MuSK MG patients, while jitter analysis shows high sensitivity, especially in facial muscles. The EDC muscle in MuSK MG patients usually shows increased jitter in more severe disease forms and later in the course of the disease.